Individual Networks of Practice for PhD Research Socialisation - Watson Todd, Richard; Louw, Stephen (Journal of University Teaching and Learning Practice, 2019)
A PhD combines experiential learning of the research process with socialisation into the research community. Studying a PhD is a highly individual experience with each student seeking and receiving different types of support from different agents. In this paper we investigate the experiences of four PhD students at a Humanities faculty at a Thai university through a series of interviews. To account for the unique nature of each student’s experience, we use Individual Networks of Practice (INoPs) as the main method of analysis. The interviews were first analysed by adapting Sala-Bubaré and Castelló’s (2016) model of socialisation, identifying the social agents and the content of the experience shared with each agent, and then constructing an INoP (Zappa-Hollman and Duff 2015) map to visually represent each student’s social network. These INoPs served to guide a qualitative analysis of the salient issues in the interviews. The INoPs highlight the unique nature of each student’s set of agents and experiences, but there are also commonalities across students showing that peers and faculty staff serve as key social agents.